Design and Development of the Portable Solar Fan - Abdul Rahman, Muhammad Danial Asyraf; Mohd Zaid, Muhammad Hud Zakwan; Rosli, Nurul Asma Aqilah; Janon, Mohd Najib; Mohamad, Mahmod Abd Hakim; Mohammad Noor, Hafsa (Multidisciplinary Applied Research and Innovation, 2025)
The demand for sustainable and portable cooling solutions has grown significantly with rising global temperatures and increased outdoor activity. Traditional electric-powered fans often lack mobility and rely heavily on non-renewable energy sources, creating a need for more environmentally friendly alternatives. This project addresses that gap by designing and developing a portable solar-powered fan that emphasizes energy efficiency, ease of transport, and user comfort. The objective is to create a device that utilizes solar energy to provide consistent airflow for personal cooling, particularly in off-grid or outdoor settings. The fan was developed through a structured design process, selecting lightweight and durable materials, integrating a solar panel, and including a rechargeable battery system. Several design iterations and experimental testing were evaluated based on battery life, structural integrity, and ergonomic handling. Results indicate that with a full charge of 5 bars, the battery provides a total runtime of approximately 11.92 hours. Also, the charging characteristic of the battery is notably efficient, approximately 53 minutes to charge, resulting in a total charging time of around 4.42 hours from empty to full. During operation, the battery maintains a stable voltage output within the range of 12V to 12.5V. The design successfully balances functionality and portability, although improvements are needed in structural rigidity. In conclusion, the portable solar fan demonstrates a practical application of renewable energy in daily-use appliances and highlights potential for further development in sustainable consumer product design.